Advokasi Public Relations dalam Program Pemberdayaan Penyandang Disabilitas - Fathiya Nur Rahmi; Hanny Hafiar; Iriana Bakti (Jurnal Riset Komunikasi (JURKOM), 2022)
This study aims to determine the implementation of public relations advocacy through empowerment programs for persons with disabilities. The method used in this research is qualitative with a case study approach. Data collection techniques used interviews, observation, and documentation and researchers used flow analysis models for data analysis techniques. The result of this research is that there are principles used in the empowerment program, namely using a twin-track approach or a two-way approach, people with disabilities, and job providers. The empowerment program starts from planning by conducting a situation analysis. The form of implementation of the empowerment program consists of job readiness training, strengthening alumni careers, digital training, and panel discussions. Suggestions in this research in the future Saujana NGO can carry out public categorization specifically so that public needs and interests can be met. As well as optimizing collaboration with communities and NGOs that can help implement the value of inclusion for persons with disabilities, especially in terms of accessibility of job opportunities.